The Future of Education Related to SDG 16 (Peace, ‎Justice, and Strong Institutions) - Kowkas, Sultan; Shayeb, Shaheen; Bransi, Narmeen (Buletin Edukasi Indonesia, 2024)
The spreading aspects of the seventeen sustainable development goals have been of concern to ‎researchers in education worldwide. These goals have shed light on and captured the attention of ‎very crucial issues. The significance of these issues (the core of each SDG) lies in their ‎importance, connectedness, and mutual influence on each other. Education, ‎ the highest peak of achievement in every society, and hence in the whole (small) world, is ‎directly affected by each SDG. That was the reason for considering the future of Education in sight ‎of one of the most influential sustainable goals, namely, peace, justice, and strong institutions. The ‎current paper is a position paper that discusses the float of the sixteenth sustainable goal along the ‎future of Education. The researchers propose two statements: firstly, SDG 4 (Quality Education) ‎and SDG 16 possess a reciprocal interaction property (i.e., mutually impact each other). ‎Secondly, this cyclic process has to start by first accomplishing SDG 16‎‏.